Coastal hypoxia and eutrophication as key controls on benthic release and water column dynamics of iron and manganese. Issue 3 (14th November 2020) - Lenstra, Wytze K.; Hermans, Martijn; Séguret, Marie J.M.; Witbaard, Rob; Severmann, Silke; Behrends, Thilo; Slomp, Caroline P.
Abstract: Continental shelves are a major source of iron (Fe) and manganese (Mn) to marine waters. Here, we investigate controls on benthic release of Fe and Mn and the impact on the water column in the Baltic Sea. We find high in situ benthic release rates of dissolved Fe and Mn at seasonally hypoxic sites (bottom water oxygen between 0–63 μ mol L −1 ) receiving high inputs of organic matter. We find that benthic Fe and Mn release is sensitive to bottom water oxygen concentrations. Benthic Fe release is likely additionally controlled by Fe–sulfur redox chemistry in the surface sediment. For Mn, benthic release correlates positively with Mn oxide availability in the surface sediment. Benthic release contributes to high dissolved Fe and Mn concentrations in the water column and is amplified by repeated cycling of Fe and Mn between the sediment and overlying water through benthic release, oxidation in the water column, deposition as metal oxides, followed by reductive dissolution. Most water column Fe (∼ 80%) is present in particulate form near the seafloor. In contrast to Fe, a large percentage of the Mn remains dissolved (∼ 50%). We show that easily reducible Fe and Mn oxides are key forms of particulate Fe and Mn in suspended matter. The Baltic Sea represents a highly eutrophic, low oxygen end‐member when compared to other modern coastal systems. Our results imply that, upon continued eutrophication and deoxygenation of the coastal ocean, benthic release of dissolved Fe and Mn from continental shelves could become greater than previously thought.